2007
DOI: 10.1089/lap.2006.0235
|View full text |Cite
|
Sign up to set email alerts
|

A New Technical Approach for Extraperitoneal Laparoscopic Bladder Diverticulectomy

Abstract: In this paper, the authors report on a new, modified laparoscopic technique to remove a large bladder diverticulum. A 26-year-old male with a urinary problem underwent an ultrasound, as well as intravenous urography and cystoscopy examinations, which showed a large bladder diverticulum. The diverticulum was operated upon laparoscopically. The extraperitoneal laparoscopic intervention was facilitated by balloon placed into the diverticulum. The new technique for the laparoscopic diverticulumectomy procedure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The diverticulum is flattened due to pneumoperitoneum, challenging easy recognition. Several maneuvers and techniques have been defined to facilitate the identification of the diverticulum during the procedure [5,6,10,11,12,13,14,15]. Moore et al [10] instilled methylene blue into the bladder to aid in intra-abdominal identification of the diverticular neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverticulum is flattened due to pneumoperitoneum, challenging easy recognition. Several maneuvers and techniques have been defined to facilitate the identification of the diverticulum during the procedure [5,6,10,11,12,13,14,15]. Moore et al [10] instilled methylene blue into the bladder to aid in intra-abdominal identification of the diverticular neck.…”
Section: Discussionmentioning
confidence: 99%
“…Nadler et al [12] placed a home-made balloon catheter inside the diverticulum and inflated the balloon in the diverticulum. Flasko et al [13 ]also placed a home-made balloon into the diverticulum, but through the working channel of a nephroscope. Shah et al [14 ]and Khonsari et al [15 ]inserted a guide wire into the diverticulum and placed catheters over the guide wire.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic or robotic diverticulectomy is the preferred method due to excellent efficiency and minimal invasiveness and morbidity. Laparoscopy can be extraperitoneal [ 6 , 8 ], intraperitoneal (= transperitoneal) [ 2 , 3 ] or suprapubic transvesical [ 18 20 ]. Pure laparoscopy can be replaced by robotic-assisted bladder diverticulectomy [ 1 , 9 , 11 , 12 , 14 , 18 , 19 , 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been several reports of laparoscopic bladder diverticulectomy in adults [13][14][15][16][17][18], we have located only one previous report on pediatric laparoscopic extravesical bladder diverticulectomy in the literature that also described concurrent nephroureterectomy in a 6-year-old child [19]. In this approach, identification of the diverticulum from outside of the bladder can be difficult [15].…”
Section: Extravesical Laparoscopic Surgerymentioning
confidence: 95%
“…Rebouças et al reported that the concomitant use of cystoscopy facilitates the identification and location of the diverticulum, thereby minimizing dissection of the bladder and decreasing operative time [17]. Flasko et al reported that the introduction of a balloon into the diverticulum makes the operation easier during laparoscopic extravesical bladder diverticulectomy [18].…”
Section: Extravesical Laparoscopic Surgerymentioning
confidence: 99%